2014
DOI: 10.1016/j.micres.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle and spore resistance of spore-forming Bacillus atrophaeus

Abstract: Bacillus endospores have a wide variety of important medical and industrial applications. This is an overview of the fundamental aspects of the life cycle, spore structure and factors that influence the spore resistance of spore-forming Bacillus. Bacillus atrophaeus was used as reference microorganism for this review because their spores are widely used to study spore resistance and morphology. Understanding the mechanisms involved in the cell cycle and spore survival is important for developing strategies for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 84 publications
2
47
0
4
Order By: Relevance
“…The B. pumilus species belonging to the B. subtilis group is ubiquitous both in the terrestrial and marine ecosystems. This bacterium is highly resistant to extreme environmental conditions, such as low or no nutrient availability, desiccation, irradiation and chemical disinfections (Fritze, 2004;Menezes et al, 2010;Sella, Vandenberghe, & Soccol, 2014). There are several previous reports confirming that some B. pumilus strains are capable of causing diseases in pears (Li et al, 2009), peaches (Saleh, Huang, & Huang, 1997), mangoes (Galal, El-Bana, & Janse, 2006), Ficus lacor (Hakim, Liaquat, Gul, Chaudhary, & Munis, 2015) and pine tree (Kovaleva, Shalovylo, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The B. pumilus species belonging to the B. subtilis group is ubiquitous both in the terrestrial and marine ecosystems. This bacterium is highly resistant to extreme environmental conditions, such as low or no nutrient availability, desiccation, irradiation and chemical disinfections (Fritze, 2004;Menezes et al, 2010;Sella, Vandenberghe, & Soccol, 2014). There are several previous reports confirming that some B. pumilus strains are capable of causing diseases in pears (Li et al, 2009), peaches (Saleh, Huang, & Huang, 1997), mangoes (Galal, El-Bana, & Janse, 2006), Ficus lacor (Hakim, Liaquat, Gul, Chaudhary, & Munis, 2015) and pine tree (Kovaleva, Shalovylo, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The heat causes damages in bacterial spore cells, and the heated spores’ deformations and damages, and the release of intracellular components (Rozali et al ). However, they still have the ability to germinate after sublethal injury, and their suitability for genetic manipulation are of practical importance for food sterilization processes (Sella et al ). Our results also showed that just alone thermal processing could not kill all bacteria or inhibit bacterial growth and it required multiple methods to work together.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus-based probiotics present an advantage because of the inherent resistance of Bacillus spores (40). Although the Bacillus clausii preparation Enterogermina has been described as an antidiarrheal that also prevents antibiotic-associated diarrhea (28,29), data describing the functional mechanisms remain very limited.…”
Section: Discussionmentioning
confidence: 99%